PASS Theory and Movement Disorders: Methodology for Assessment and Intervention - Katerina Asonitou; Dimitra Koutsouki (MDPI AG, 2024)
Background/Objectives: Executive dysfunction appears to be a significant secondary characteristic frequently linked with movement disorders. Planning is a high-level cognitive process integral to our executive functions. Children who show deficits in their planning ability usually have difficulties in making decisions or problem-solving, such as initiating tasks or mentally organizing a project, and monitoring and controlling their behavior effectively. These difficulties can significantly impact their academic performance and daily functioning even in adulthood. However, the existing research on the relationships between motor performance and planning abilities is limited and inconsistent. Methods: This study aimed to explore the potential associations between motor and planning skills in 30 preschool-aged children with Developmental Coordination Disorder (DCD) and 30 healthy controls matched for age, including utilizing the PASS theory and Cognitive Assessment System (CAS). Results: The findings highlighted balance, total motor score, and planned codes as the primary factors distinguishing the two groups. A significant Pearson's correlation was observed between the overall MABC-2 scores and the subdomain scores, along with the Planning Scale indices for both groups, suggesting a substantial relationship between these assessments. Among the Planned codes items, the most notable predictor of overall motor performance in children was identified. Furthermore, the total score for Planned Connections emerged as the most robust predictor for tasks associated with manual dexterity. Conclusions: The relationship between motor skills and executive functions in early childhood plays a vital role in the development of early intervention strategies that utilize cognitive-motor tools.